Recent Applications in the Use of Sulfoxides as Chiral Auxiliaries for the Asymmetric Synthesis of Natural and Biologically Active Products - Salom-Roig, Xavier; Bauder, Claude (Synthesis, 2020)
The contribution of chiral sulfoxides as versatile auxiliaries in the field of organic chemistry has shown a prevalent interest in the asymmetric synthesis of natural products during the last 45 years. In this short review, we report the recent applications of these chiral auxiliaries to the synthesis of natural and biological active products highlighted from 2010 to 2019. We hope to allow the reader to have an overview of the potential of sulfoxide chemistry in the field of enantioselective synthesis.1 Introduction2 Diastereoselective Additions to Ketones2.1 Reduction of β-Keto Sulfoxides2.2 Reduction of β-Keto Sulfoxides Followed by Bromohydrin Forma tion3 Synthesis of an α-Amino α′-Sulfinyl Ketone Followed by Diastere oselective Reduction of the β-Keto Sulfoxide4 Diastereoselective Addition of Carbanionic Chiral Sulfoxides4.1 Addition to an Aldehyde4.1.1 Aldol Reactions4.1.2 Reformatsky-Type Reactions4.2 Additions to Chiral Sulfinimines5 Diastereoselective Cyclization Reactions Directed by a Chiral Sulf oxide5.1 1,4-Radical Additions5.2 Intramolecular Conjugate Additions5.3 Nazarov Cyclizations5.4 Diels–Alder Reactions6 Atropodiastereoselective Synthesis7 Conclusion
Keywords: chiral sulfoxides; asymmetric synthesis; diastereoselectivity; natural products; methodology